Tankar om plöjningsfri odling - Westöö, Magnus (2005)
The margin in crop production is more and more less and it forces the producer to check out how to reduce the cost of establishment of new crop. One way to reduce the cost in establishment is to begin with plough less farming. It saves money and time compares to conventional soil preparation with plough and harrow. Not all soil types are god for plough less farming and should be continued with ploughing (mainly light soil), but other soil types working very well with plough free farming. If you want to success with plough less farming you have to think in new lanes. One of the things you have to think about is to not grow too much cereal after cereal. Low stubble is important when you harvest the crop and also to spread and chop the straw well. I have in this work interviewed some farmers and farm advisers in Östergötland to see which thoughts they have about plough less farming. It has been farmers who not plough at all to farmers who plough almost everything. The main theme for those who use their plough is that they try to aware the plough after crop that not give so much straw like peas and colza but they plough before and after the cereals. They think it is going to be more plough less farming in the future. The farmers who already skip the plough think it works very well and will continue to skip the plough.